2020
DOI: 10.1038/s41467-020-15515-2
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated dryland expansion regulates future variability in dryland gross primary production

Abstract: Drylands cover 41% of Earth's surface and are the largest source of interannual variability in the global carbon sink. Drylands are projected to experience accelerated expansion over the next century, but the implications of this expansion on variability in gross primary production (GPP) remain elusive. Here we show that by 2100 total dryland GPP will increase by 12 ± 3% relative to the 2000-2014 baseline. Because drylands will largely expand into formerly productive ecosystems, this increase in dryland GPP ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(97 citation statements)
references
References 61 publications
(79 reference statements)
3
88
0
Order By: Relevance
“…This phenomenon is similar to the principle of regulated irrigation in agriculture to increase water use efficiency under a certain degree of water stress (Chai et al, 2016), and also revealed by other studies (Zhang and Zhang, 2019). This dryness effect on ecosystem productivity cannot be detected in the annual scale assessment (Brookshire and Weaver, 2015;Yao et al, 2020). These results indicate firstly that pre-growing season hydroclimate conditions play a key role in the follow-on vegetation growth and production (Wang et al, 2019), and secondly that water limits vegetation even in this subtropical rain-abundant region instead of water shortage resulted from vegetation establishment.…”
Section: Causal Roles Of Water and Dryness In Vegetation Changessupporting
confidence: 77%
“…This phenomenon is similar to the principle of regulated irrigation in agriculture to increase water use efficiency under a certain degree of water stress (Chai et al, 2016), and also revealed by other studies (Zhang and Zhang, 2019). This dryness effect on ecosystem productivity cannot be detected in the annual scale assessment (Brookshire and Weaver, 2015;Yao et al, 2020). These results indicate firstly that pre-growing season hydroclimate conditions play a key role in the follow-on vegetation growth and production (Wang et al, 2019), and secondly that water limits vegetation even in this subtropical rain-abundant region instead of water shortage resulted from vegetation establishment.…”
Section: Causal Roles Of Water and Dryness In Vegetation Changessupporting
confidence: 77%
“…This region accounts for less than half of the land but more than 70% of the annual mean GPP. This delineation in GPP roughly coincides with the location of drylands in CONUS that are more sensitive to changes in precipitation; drylands are also projected to expand in future climate (Yao et al, 2020). Most of the large year-to-year differences occur in these western US drylands (see Fig.…”
Section: Identifying Distinct Relationships Between Sif and Gppmentioning
confidence: 58%
“…Drylands comprise 45% of the terrestrial earth surface (Prăvălie, 2016), and precipitation is the most limiting factor to the functioning of dryland ecosystems (Lauenroth, 1979;Noy-Meir, 1973). Therefore, their responses to interannual precipitation variability have important consequences for global patterns of productivity (Ahlström et al, 2015;Gherardi and Sala, 2019;Yao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%